TEACHING EFL TO MIXED-ABILITY CLASSES: STRATEGIES, CHALLENGES, SOLUTIONS - Hordiienko, N. M.; Lomakina, L. V. (Advanced Education, 2015)
This article deals with the challenges English language teachers regularly face when working with so-called mixed-ability classes. The analysis of the main strategies presented by leading local and foreign scientists concerning the problem of teaching to different-level students in technical higher educational establishments is carried out. The article focuses on the importance of the problem mentioned as well as probable reasons of the prevalence of the problem. Taking into consideration the deficiency of system development of methods and approaches to teaching English in mixed-ability classes, the following scientific research is focused on scrutinising all sorts of possible solutions of the problem arising from the necessity to teach English in mixed-ability groups. The attempt to investigate strategies and methods that can be successfully applied in the process of English language teaching in mixed-ability groups was undertaken. The role of peer tutoring as one of the feasible solution of the problem is examined. The vital importance of facilitating favourable friendly atmosphere in the mixed-ability class is highlighted. The necessity to develop assignments of different levels of complexity presenting challenge for advanced students and not frustrating and demotivating the average ones is mentioned. Students’ psychological problems arising in the process of learning a foreign language in different-level groups, particularly, in the process of improving communication skills, are considered. The article is of great help to all foreign language teachers interested in effective implementation of modern techniques and approaches that can have a positive impact on the teaching process in mixed-ability classes.